Ultrastrong, flame-retardant, intrinsically weldable, and highly conductive metallized Kevlar fabrics. Issue 40 (29th September 2022) - Lu, Xi; Ye, Yusheng; Shang, Wenhui; Huang, Simin; Wang, Haifei; Gan, Tiansheng; Chen, Guokang; Deng, Libo; Wu, Qixing; Zhou, Xuechang
Abstract : Ultrastrong, flame-retardant, intrinsically weldable, and highly conductive metallized Kevlar fabrics (MKF) were fabricated via polymer-assisted electroless deposition and electrodeposition techniques. Abstract : Conductive textiles are promising components for next-generation wearable electronics. However, it is still a challenge for current conductive textiles and wearable electronic devices to survive in harsh environments, such as extreme mechanical damages and low/high-temperature stresses. Herein, we report ultrastrong, flame-retardant, intrinsically weldable, and highly conductive metallized Kevlar fabrics (MKFs) fabricated via polymer-assisted electroless deposition (ELD) and electrodeposition (ED) techniques. The combination of ELD and ED techniques effectively metallizes the Kevlar fabrics, enabling ultrahigh conductivity (sheet resistance <0.007 Ω sq −1 ). More importantly, the deposited metal layers significantly enhance the anti-impact properties of Kevlar fabrics by 2–3 times. Due to the inherent properties of Kevlar and effective metal coatings, the MKFs maintain conductivity while suffering various mechanical damages (GPa-scale tensile strength, cutting, sticking, etc. ), high temperatures (∼300 °C), and even flame stresses. Surprisingly, the MKFs show intrinsic weldability with traditional solder materials. The multifunctional applications of such high-performance metallized fabrics are demonstrated as textile-based conductors, heaters, and supercapacitors, all of which could survive in extremely harsh conditions.